Chinese herbal medicine Wutou decoction for knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 43 (23rd October 2020) - Zhou, Xing; Xiang, Kemeng; Yuan, Xiangyao; Wang, Zhenping; Li, Kuanglin
Abstract: Background: Knee osteoarthritis (KOA) causes joint pain and limited mobility, which affects the quality of life. The use of Chinese herbal medicine to treat KOA has achieved certain effects, and Wutou decoction (WTD) is one of them. But there is no high-level evidence to support this result. The purpose of this work is to evaluate WTD's efficacy and safety in the management of KOA. Methods: We will search articles in 7 electronic databases including Chinese National Knowledge Infrastructure (CNKI), Wanfang Data (WF), Chinese Scientific Journals Database (VIP), Chinese databases SinoMed (CBM), PubMed, Embase, and Cochrane Library databases. All the publications, with no time restrictions, will be searched without any restriction of language and status, the time from the establishment of the database to September 2020. Two reviewers will independently assess the quality of the selected studies, NoteExpress and Excel software will be used to extract data, and the content will be stored in an electronic chart. Different researchers will separately screen the titles and abstracts of records acquired potential eligibility which comes from the electronic databases. Full-text screening and data extraction will be conducted afterward independently. Statistical analysis will be conducted using RevMan 5.4 software. Results: This study will evaluate the current efficacy and safety of WTD in the treatment of KOA, to provide high-quality, evidence-based clinical recommendations. Conclusion: This study will provide reliable evidence on whether WTD is safe and effective in treating KOA. Trial registration number: INPLASY202090022